(3cJGH GhWhdhbS aj GdWdhY hGdZQhHs - (3GhWhdhbSs
(3ChdgG (B:s
(3jbGd dHYV WdhYGJ GdchGcH hZQhHGJgG hNUhUkG GdKhGHJ GfgG NajI hdHYVgG GfgG XGgQI s
(3BNQgG (B:s
(3hcd chcH jJeGjd YfgG aGfg jMOK ai GcKQ ef Pdc hcd chcH LfhHi YfgG eG jMOK heYg Je HJeGegG cJGH ChWhdhbS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3GfXQg eY GdeNWhW Qbe (B66 (3ef faS GdHYKIs
(3HgG CTcGd gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1435s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(10/2432) s
Keywords: (3Gdadcs